Maladaptive nest‐site selection and reduced nest survival in female sage‐grouse following wildfire. Issue 12 (4th December 2022) - Dudley, Ian F.; Coates, Peter S.; Prochazka, Brian G.; Davis, Dawn M.; Gardner, Scott C.; Delehanty, David J.
Abstract: Increased wildfire frequency and associated replacement of sagebrush ( Artemisia spp.) with invasive annual grasses contribute to declines of greater sage‐grouse ( Centrocercus urophasianus ; hereafter, sage‐grouse) populations across the Great Basin. However, little is known about wildfire effects on sage‐grouse nest‐site selection and nest survival, which can influence population persistence. The primary objective of this study was to evaluate the effects of the Rush Fire on sage‐grouse nest survival using before (2007–2009) and after (2015–2018) data collected from a population of sage‐grouse occupying the border of northeastern California and northwestern Nevada. We employed a before–after–control–impact (BACI) experimental design to account for spatiotemporal heterogeneity in the system and to derive estimates of relative change in survival parameters. Sage‐grouse nest survival decreased after the Rush Fire but decreased more in the burned area relative to the unburned area. Although female sage‐grouse continued to occupy burned areas, nest survival was reduced from 52% to 19%. Using a BACI ratio approach we found that nest survival decreased approximately 51% in the burned area, relative to the unburned area, following wildfire. Habitat analyses were restricted to the postfire period and found that female sage‐grouse that nested within unburned areas selected for wider nesting substrate, taller perennial grass height, and greater low sagebrush canopy cover. Conversely, female sage‐grouse that nested in burned areas used shorter sagebrush canopy cover than what was available across the entire study area but showed stronger selection for perennial grass height than their unburned counterparts. Strong nest‐site fidelity in sage‐grouse may explain the continued use of suboptimal habitat in wildfire‐altered landscapes, resulting in a reproductive cost, and overall reproduction well below replacement rate. Results suggest that fire suppression or rapid postfire habitat restoration, especially within nesting habitat, may be essential to conserving robust sage‐grouse populations into the future.